Outcomes of oncologic robotic gastrectomy compared with open gastrectomy for early and locoregional advanced gastric cancer. (1st June 2022) - Jung, M K; Chevallay, M; Toso, C; Mönig, S P
Abstract: Objective: Minimally invasive gastrectomy for gastric cancer shows slower adoption in Western countries compared to Asia, probably due to lower incidence, advanced stages and a more frequently proximal localization, which requires a technically more challenging total gastrectomy. Methods: We retrospectively reviewed a prospectively collected database. A total of 51 patients who underwent oncologic total gastrectomy or subtotal gastrectomy by robotic or open approach of stage pT1-T4a, pN0-3 were identified from June 2016 until June 2020. Nine patients were operated on robotically, and 42 patients by laparotomy. Perioperative outcomes, postoperative 30-day complications as well as pathologic results were compared. Results: The age of the patients in the robotic group was comparable to that of the open group (64.7 ±9.2 versus 62.8 ±12.9, respectively, p = 0.685). Blood loss was significantly smaller with the robotic approach (185±180 mL versus 425±257 mL, p = 0.038). Pathologic tumor stage included stages pT1–pT4b in the open group, while only stages pT1–pT3 were operated by robotic approach. Fewer tumors were localized in the upper body in the robotic group (0, 0%) than in the open group (12, 28.6%). The length of the proximal margin was comparable in the two groups (104.29 ± 50.29 versus 86.88 ± 64.66, p = 0.516). The mean number of retrieved lymph nodes was comparable in the robotic group and the open group (42.89 ± 12.119 versus 43.22 ± 20.271, p = 0.963). The mean number of metastatic nodes was significantly lower in the robotic group (0.33 ± 0.707 versus 7.02 ± 14.313, p = 0.171). In regards to Lauren classification, diffuse-type cancers were significantly more frequent in the robotic group (3 (33.3%) versus 3 (8.6%), respectively, p = 0.040). Significantly fewer high-grade complications (Clavien/Dindo >3a) appeared in the robotic group (0 (0%) versus 2 (4.8%), p = 0.019). No anastomotic leakage and no death occurred in both groups. Conclusion: The gold standard of oncologic gastrectomy, especially for advanced stages and bulky lymph nodes, is still the open approach. The minimally invasive approach for gastric cancer may be beneficial in regards to blood loss and postoperative complications but must show comparable pathohistological results in comparison to the open approach in regards to lymph node harvest and proximal tumor margins to be an acceptable alternative to the open approach.